A matched cohort comparison of cervical disc arthroplasty versus anterior cervical discectomy and fusion: Evaluating perioperative outcomes. (September 2017) - Upadhyayula, Pavan S.; Yue, John K.; Curtis, Erik I.; Hoshide, Reid; Ciacci, Joseph D.
Highlights: CDA performs comparably to ACDF in a matched cohort analysis. CDA operations were shorter and patients were more likely to be discharged home. There was no difference in complication or reoperation rates between CDA and ACDF. Abstract: Objective: Cervical disc arthroplasty (CDA) is a recent alternative to anterior cervical discectomy and fusion (ACDF) in patients suffering cervical disc herniation and degeneration. To date, a systematic analysis of their comparative advantages and risks following elective surgery remains elusive. Methods: Adult patients undergoing elective CDA or ACDF were extracted from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database years 2011–2014. A total of 19, 369 patients were matched 1:1 by age, sex, functional status, charlson comorbidity index, ASA classification, BMI classification, and number of vertebral levels operated on during surgery. This matching process led to a final sample of 588 subjects (294 CDA, 294 ACDF). Multivariable regression was performed for five outcome measures: operation time, early complications, reoperation rates, hospital length of stay (HLOS), and discharge destination. Mean differences ( B ), odds ratios (OR) and associated 95% confidence intervals (CI) are reported. Results: Compared to ACDF, CDA was associated with decreased mean operation time ( B  = −18.78-min, 95% CI [−29.13, −8.42]; p  < 0.001), decreased HLOS ( B  = −0.44-days [−0.77, −0.11]; p  = 0.009), and increased likelihood of discharge to home (OR = 5.39 [1.14–25.43]; p  = 0.033). No differences in reoperation rates and complications were found. Conclusion: In a matched cohort analysis, CDA performs comparably to ACDF and is associated with decreased operation time and HLOS, and increased likelihood of discharge to home, without differences in 30-day complications or reoperation rates. Future prospective studies are warranted.